Lady Jane - Trevor, Nunn.; Elwes, Cary, 1962-; Jane Lapotaire; Jill Bennett; John Wood; Michael Hordern; Sara Kestelman; Helena Bonham Carter (UK Capital Equipment Leasing, 1986)
The death of King Henry VIII throws his kingdom into chaos because of succession disputes. His weak son Edward, is on his deathbed. Anxious to keep England true to the Reformation, a scheming minister John Dudley marries off his son, Guildford to Lady Jane Grey, whom he places on the throne after Edward dies. At first hostile to each other, Guildford and Jane fall in love. But they cannot withstand the course of power which will lead to their ultimate downfall.
The death of King Henry VIII throws his kingdom into chaos because of succession disputes. His weak son Edward...
Chris Bryant
Language(s): English, Italian
Subtitle(s): English, Turkish, Arabic, Serbo-Croatian, Slovenian
Keywords: History; Drama